Penegakan Hukum yang Berkeadilan - Rafli Dwilianto; Alya Arrahmah; Intan Yulia Putri; Alwi Usman Matondang; Bambang Trisno (International Forum of Researchers and Lecturers, 2024)
This research aims to explain fair law enforcement. Our data sources in this journal come from relevant and reliable literature, namely primary data sources from citizenship and Pancasila books as well as supporting journals as secondary data sources. The research method used in this journal is a qualitative library research method. The data analysis technique applied is analysis of the content and core of the research, which aims to maintain the integrity of the research process and prevent errors in understanding. The presentation of this research is structured simply to make it easier for readers to understand the essence of the material discussed in this research.